Penggunaan Gigi Tiruan pada Lansia dengan Obstructive Sleep Apnea - Chandra Dwidjayanti, Siti; Kurniawati, Isnaeni; Marpaung, Carolina (Jurnal Kedokteran Gigi Terpadu, 2024)
A person who has reached the elderly stage will have an experienced degenerative process that causes several disorders. Changes in the masticatory function due to the loss of the remaining teeth can cause a transformation not only in the mastication system but also in the upper airway system of respiration. This is due to orofacial deformation, tongue retraction while in the resting position, occlusal vertical dimension changes, and a decrease in facial height. Obstructive Sleep Apnea (OSA) is a sleep breathing disorder with 17 % prevalence rate in adults and increases up to 49% in the elderly stage. A complete denture can be a rehabilitative treatment option for the elderly OSA patient. Wearing dentures during sleep is against the principles of dentistry because it can cause the tongue to be positioned posteriorly. However, people, mostly women, still wears denture while sleeping. This might further increase the obstruction of upper airway system.